Enzymatic Hydrolysis of Sago Starch for the Production of Maltodextrins - Ch'ng, Yan Eng (1995)
Maltodextrin is a partial starch hydrolysis product used widely in food. It has been produced from corn, tapioca and potato starches. This project was designed to study the production of maltodextrin from refined sago starch and to characterise the maltodextrins produced. The refined sago starch used was obtained from different sago factories and labelled as Bag A, B, C, D, E, F, G, H and I. Studies carried out showed that there were variations in the quality of the starch of different bags. The moisture content of the starch varied from 10.05 to 15.40% (w/w) while the ash and crude fibre contents were 0. 1 1 0 to 0.930 % (w/w) and 0.040 to 0.560% (w/w) respectively. The sago starch showed greyish colour with Hunter Lab L values of 87.70 to 90.17 and pH values of 4.77 to 7.58. Particle size analysis showed that more than 99.3% (w/w) of the starch passed through the 125 urn pore size sieve. The peak gelatinisation viscosity of the starch varied between 458 to 680 BU. The sago starch showed a common pasting temperature of 74°C and an extremely low level of protein of less than 0.010% w/w. The measurement of the degree of starch damage showed that sago starch of Bags D, E, F and G were undamaged, while starch of the remaining bags had damage of up to 8% w/w. The undamaged sago starch was of two types: the high, and the low viscosity starch with peak gelatinisation viscosities of about 680 BU and 485 BU respectively. Enzymatic susceptibility studies showed that undamaged sago starch was relatively unsusceptible to alpha-amylases Termamyl 120L and BAN 240L. The degrees of hydrolysis achieved after prolonged incubation for 12 hours at 60°C were 8.6 to 12.1% w/w, and 1.8 to 2.3% w/w respectively. The raw damaged and the gelatinised undamaged sago starch had increased susceptibilities to these alpha-amylases. The degrees of hydrolysis were 17.5 to 22.1% w/ w, and about 3.0% w/w respectively, for damaged starch, and 88.3% and 76.5% (w/w) respectively, for the gelatinised starch. Viscozyme 120L when used alone (at a dosage of 0.05% w/w) or in combination with either Termamyl 120L or BAN 240L (at a dosage of 0.10% w/w) had the ability of reducing the viscosity of gelatinised sago starch. It was unable to hydrolyse either the raw or gelatinised starch. Damaged sago starch when used for enzymatic hydrolysis (by Termamyl 120L) produced unstable low DE syrups which retrograded on cooling. Sago starch with high crude fibre content produced low DE syrups that were difficult to filter. Both Termamyl 120L and BAN 240L were found to be suitable for the production of maltodextrin from sago starch. A starch concentration of 20% (w/v) was suitable for hydrolysis at pH 5.5 to pH 6.5. Optimum Termamyl 120L dosages were 0.08 to 0.10% (w/w) for the production of DE 6 to 20 maltodextrins. A dosage of 0.04% (w/w) of BAN 240L was suitable for producing DE 8 to 11 maltodextrins while 0.06% (w/w) and 0.08% (w/w) of the amylase were suitable for producing DE 12 to 15, and DE 16 to 20 maltodextrins respectively.